Recycling of graphite from spent lithium–ion batteries via low-temperature polyvinyl chloride roasting-assisted leaching - Zeng, Guisheng; Zhou, Rui; Hu, Chongwen; Zhao, Haohan; Gao, Hanxiao; Huang, Jianwen; Yu, Jiaping; Luo, Feng; Wang, Zhongbing; Deng, Chunjian; He, Junwei; Liu, Chunli (Carbon (New York), 2025)
With the widespread application of lithium-ion batteries, the recycling of lithium batteries has attracted widespread attention. Unfortunately, the low economic value of spent graphite often leads to their neglect. This work proposes a novel scheme of efficient purification and high-quality regeneration of graphite from spent LIBs by low-temperature spent polyvinyl chloride (PVC) roasting-assisted leaching. Through low-temperature PVC roasting, the metal impurities of spent graphite were converted into water-soluble metal chloride, and the roasting tail gas was absorbed by water and converted into absorption liquor. After the leaching using the absorption liquor, the purity of the purified graphite exceeded 99.9%. Subsequently, the material was reheated at 1000°C to produce regenerated graphite. The material structure, including interlayer spacing and surface morphology, were significantly repaired, aligning with those of commercial graphite. The cyclic stability had been powerfully promoted, after 500 cycles at 1 C, the specific capacity of regenerated graphite remained at 111.5 mAh/g, with a retention rate of 75% (spent graphite was 43.4 mAh/g, 33%) and a coulombic efficiency exceeding 99%, demonstrating good rate performance and cycling stability. This technology not only reduces the regeneration costs of graphite materials but also achieves environmental benefits through the principle of “treating waste with waste”. [Display omitted] •Spent graphite was purified via low-temperature PVC roasting-assisted leaching.•The purity of purified graphite is higher than 99.9%.•Material structures of purified graphite were repaired after 1000°C roasting.•Regenerated graphite exhibits excellent electrochemical performance.•Reduced regeneration costs and achieved environmental benefits through this method.